If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3X + 1 = 48 Reorder the terms: 1 + 3X = 48 Solving 1 + 3X = 48 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3X = 48 + -1 Combine like terms: 1 + -1 = 0 0 + 3X = 48 + -1 3X = 48 + -1 Combine like terms: 48 + -1 = 47 3X = 47 Divide each side by '3'. X = 15.66666667 Simplifying X = 15.66666667
| 4x+y=-x+9 | | 2x+3=61 | | 6(-2-9k)= | | 3x-1.66=-7(3.5x-3)-3 | | 2(6+5x)=102 | | 4x=81+x | | -29x+6.1=-5(5.8x+2.2)-0.3 | | a+0.05a= | | -45x-1=9(-5x+1)-4 | | -15=5x+10 | | (x+3)(x-4)=-12 | | (2x+3)(6-3x)=0 | | (-8x+8)2=4 | | (50-2x)*(25x+400)=204000 | | 34x+23.4=4(8.5x+4.1)+7 | | 7x+4y=4 | | -10x+17=-2(5x-5)+7 | | lnx+2+lnx+2=6 | | 2x-7=-14 | | log[5]5=x | | x*log[5](x)=18 | | (25k^2)=30 | | F(x+3)=x^2+kx-21 | | x^3+4x^2-19+14=0 | | x*(x-7)=228 | | =sin(9x) | | y=sin(9*x) | | 4[5x+5]=180 | | 3[5x+5]=75 | | 55=5[3x-4] | | -8x^2+16+x^4=0 | | 5[4x-3]=145 |